2018
DOI: 10.1039/c8tb00569a
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Fe(OH)3 nanoparticle-coated and rhBMP-2-releasing PLGA microsphere scaffolds for promoting bone regeneration by facilitating cell homing and osteogenic differentiation

Abstract: Iron facilitates cell homing and enhances the capacity of rhBMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…112 The safe and effective therapeutic concentration of metal ions should be achieved by controlling their release rate. 113,114 There are many methods Reproduced with permission of Elsevier. 101 to carry metal ions; for example, common loading methods include mixing with mechanical scaffold material, incorporating it into a hydrogel, coating with scaffold, and loading with a porous microsphere.…”
Section: Application Modementioning
confidence: 99%
“…112 The safe and effective therapeutic concentration of metal ions should be achieved by controlling their release rate. 113,114 There are many methods Reproduced with permission of Elsevier. 101 to carry metal ions; for example, common loading methods include mixing with mechanical scaffold material, incorporating it into a hydrogel, coating with scaffold, and loading with a porous microsphere.…”
Section: Application Modementioning
confidence: 99%
“…[ 168,176 ] Studies also confirmed the effect of other metal ions on cell proliferation, such as magnesium, which is the second most metallic element in human body. [ 177,178 ] Furthermore, Fe(OH) 3 nanoparticles incorporated into PLGA scaffolds exhibited a positive impact on BMSCs proliferation, as reported by Zhang et al [ 179 ]…”
Section: Experimental Advancesmentioning
confidence: 65%
“…[168,176] Studies also confirmed the effect of other metal ions on cell proliferation, such as magnesium, which is the second most metallic element in human body. [177,178] Furthermore, Fe(OH) 3 nanoparticles incorporated into PLGA scaffolds exhibited a positive impact on BMSCs proliferation, as reported by Zhang et al [179] The functional groups of biomaterials can also play an important role in improving adhesion and proliferation of cells. One of the most investigated representatives is graphene and its derivative GO, which have been applied in hard tissue engineering for a long time.…”
Section: Cell Proliferationmentioning
confidence: 82%
“…Integration of various biophysical/biochemical cues into microgels or utilization of signaling factors secreted by encapsulated cells or peripheral tissue cells may help to promote microgel assembly spatio-temporally in vivo. In addition, there is few researches on the combination of microgels with other subunits, such as bioactive inorganic microspheres, solid polymer microspheres, cell spheres and decellularized ECM microspheres, which may address the disadvantages of pure microgel assembly [ [88] , [89] , [90] , [91] ]; (4) Most of the present studies are focusing on the fabrication and primary biological characterization of proof-of-concept microgels and microgel assembly, the inherent connections between the properties of individual microgel (e.g., size, crosslinking density, stiffness, etc.) and those of as-formed microgel assembly (e.g., porosity, viscoelasticity, mechanical strength, etc.)…”
Section: Discussionmentioning
confidence: 99%